Atributos fisiológicos de sementes de milho submetidas a tratamentos de sementes com inseticidas e fungicidas - Graffitti, Matheus Santos (2017)
Seed treatment is extremely important to maize, mainly on disease and pest control of early stages plant growth due to its phenotypic plasticity incapacity. However, it is fundamental the understanding of chemical interactions among chemicals used for seed treatment in order to prevent seed physiological quality decrease. Thus, the objectives of this research were to analyze seed physiological characteristics as a result of different fungicide and insecticide chemical groups. The treatments were non-treated; fipronil + thiophanatemethyl + pyraclostrobin; metalaxyl-M + fludioxonil + thiabendazole; thiophanate-methyl + fluazinam; thiamethoxam; thiamethoxam + metalaxyl-M + fludioxonil + thiabendazole; imidacloprid + thiodicarb. The randomized block design was used four and three replicates was used in laboratory and greenhouse trials, respectively. The evaluated characters were potential attributes of plant vigor which comprises seed germination percentage and dry matter weight of the root shoot and of the shoot of the seedling. Seed treatment with fipronil + thiophanate-methyl + pyraclostrobin; metalaxyl-M + fludioxonil + thiabendazole; or thiophanate-methyl + fluazinam positively affected plant vigor. The insecticide Thiamethoxam may influence the performance of metalaxyl-M + fludioxonil + tibendazole in shoot dry mass and first count. However, seed germination was not influenced by any fungicide or insecticide and all chemicals listed can be used as chemical treatment of corn seeds.